Lietuvos spaudos statistika: situacija ir perspektyvos - Bliūdžiuvienė, Nijolė (Knygotyra, 2018)
[full article and abstract in Lithuanian; abstract in English] Publishing industry statistics serves as a significant indicator of the nation’s intellectual, cultural and economic achievements and is used not only for research but also for representative purposes. Today’s changes within the publishing industry transform the way statistics data are collected, categorized and displayed as well as the criteria for their reliability. Statistics data of the publishing industry are collected by various institutions, publishers‘ associations or national libraries. In Lithuania, the principal institution for the national bibliography and publishing industry statistics is the National Library.The analysis of the present-day situation with collecting and processing publishing industry statistics shows that since the 30ies of the 20th century, there has been tight relation between the institution which collects and publishes publishing industry statistics and institutions for the official statistics. Book publishing data were published in the official publication Lietuvos statistikos metraštis (“The Chronicle of Lithuanian Statistics”), the first volume of which appeared in Kaunas in 1927. It must be noted that statistics industry data were published under the heading “Statistics of Intellectual Life”.The publishing industry statistics draws on legal deposit copies delivered to the National Library following the procedure set by the Government. The legal deposit system is regulated by the present version of the Resolution of the Government of the Republic of Lithuania “On the Number of Legal Deposit Documents and Their Delivery to Libraries”, obliging producers of public information to deliver a legal deposit copy to the National Library. From the point of view of a library, a producer of public information is a publisher; therefore, “Lithuanian Publishing Industry Statistics” prepared and published by the National Library shows the number of publishers operating in Lithuania (all producers of public information who delivered legal deposit copies to the National Library are considered publishers).When comparing the official statistics with indicators from the publishing industry statistics collected by the National Library, we observe that the data presented by the National Library show a fewer number of publishers (approximately by 10%). It must be noted that according to the National Library, the category of publishers includes all business companies and ancillary publishers, i.e. persons or organizations for which publishing is a subsidiary activity, e.g. academies,universities, research, political, religious, sports and other organizations as well as economic and commercial institutions which delivered legal deposit copies to the National Library.Absence of a universally comprehended and calculated statistical indicator for publishing industry and precise data of the print run leads to bias in derivative and summarized data. We must consider tendencies in modern publishing technologies, which might render it difficult or impossible to indicate print run, e.g. printing on demand, when books or brochures are printed by computer on somebody’s demand or when publishing items are produced by using other modern means and there is no limited or finite number of print run. In such cases we ought to find ways how to calculate statistical data for publications produced by modern technological means and how to publish them. We must broaden our understanding of publishing industry statistics by shifting it towards publishers’ statistics and covering all the data as required by the standard LST ISO 9707:2011 Information and documentation – Statistics on the production and distribution of books, newspapers, periodicals and electronic publications (identical to ISO 9707:2008). The standard presents recommendations on collecting statistical data about published books, newspapers, periodicalsand electronic publications and focuses on the collection and analysis of publishing industry data. A systematic approach to collecting such statistical data would allow to objectively analyze Lithuania’s publishing market, foresee upcoming trends and plan the publishing processes.The National Library, as a 21st century institution, is not only a contributor of statistical data but also producer of statistical reports; therefore, it should meet the requirements which pertain to a national statistical institution. Official statistics is subjected to legal regulation of the European Union. An objective has been set to build a European statistics system in order to present comparable statistical data on the European level; therefore, trustful and comparable statistical data are needed for planning and implementing such a system. The National Library, as a producer of official statistics, should persistently improve the quality of the statistical information that it prepares and processes in? preparing statistical data as well as take effort to make statistics client-oriented, precise, trustful, prompt, compatible, comparable, available and transparent.Numerous contemporary economic, as well as legal and technological, changes are no exception within the multifaceted sphere of the publishing industry. In order to achieve precise statistics of the national book industry and overall publishing industry, there must be close collaboration and mutual trust in delivering legal deposit copies as well as effort should be taken to find new ways to collect and distribute statistical data. Once publicly presented, statistical figures ofthe publishing trade become visible and universally accessible from the National Bibliography Data Bank and publications of the national bibliography and publishing statistics. [straipsnis ir santrauka lietuvių kalba; santrauka anglų kalba] Straipsnyje aptariama Lietuvos spaudos statistikos duomenų rinkimo ir apdorojimo dabartinė situacija ir galimos perspektyvos, atsižvelgiant į besikeičiančias leidybos formas ir privalomojo egzemplioriaus pateikimą Nacionalinei bibliotekai bei statistikos duomenų sklaidą. Šiuolaikiniai leidybos pokyčiai iš esmės keičia leidybos statistikos duomenų surinkimą, grupavimą, jų pateikimą ir patikimumą. Leidybos sektoriaus statistika yra oficialiosios statistikos dėmuo, todėl kreipiamas dėmesys į jos pateikimo ypatumus ir keliamus reikalavimus statistiniam tyrimui.